Efficacy of Temporalis Myofascial Flap in Maxillofacial Reconstruction - Shikder, Muhammad Sohag; Hasan, Md Mokerrom; Masud, Abdullah Al; Haider, Ismat Ara; Ahmed, Mohiuddin (Journal of Bangladesh College of Physicians and Surgeons, 2015)
Temporalis myofascial flap holds great promise for the reconstruction of various defects of the maxillofacial region for its dependable blood supply, proximity to the maxillofacial region, possibility to mobilize it to the oral cavity and its fanned out nature. The purpose of the study was to evaluate the efficacy of temporalis myofascial flap in maxillofacial reconstruction.This cross sectional study was carried out in the Department of Oral and Maxillofacial Surgery, Dhaka Dental College and Hospital from January 2011 to December 2011. Nineteen patients (10 male and 9 female), age ranging from 19 to 55 years with medium to large defect (>8cm)were selected for this study. After surgical resection of the pathological lesion, the TMF was exposed by a hemicoronal incision with a preauricular extension. The muscle was rotated to oral cavity and sutured with defect margin. Post-operatively the patient were clinically evaluated at 1, 2, 3 weeks and 1 and 3 months. Complete flap take was observed in 84% cases where as partial flap take was seen in 16% cases. Mouth opening restriction were 2-3 mm in 10 cases and 5-8 mm in 5 cases.Temporalis myofascial flap is a useful, reliable and versatile option for reconstruction of moderate to large sized defects. This flap provide abundant tissue, with minimum to no functional morbidity or esthetic deformity in donor site. J Bangladesh Coll Phys Surg 2014; 32: 78-83